2021
DOI: 10.1111/coa.13889
|View full text |Cite
|
Sign up to set email alerts
|

One dose of preoperative, intravenous, prophylactic antibiotics significantly lowers postoperative infection rate in septoplasty—a study of 772 operations

Abstract: Objectives: Postoperative infection is the most common complication after septoplasty. Pre-or postoperative prophylactic antibiotics are commonly used, although no official guidelines exist. Design:We retrospectively collected data on postoperative infections from 772 septoplasties performed in 2015, 2016 and 2018, and classified the infections according to surgical site infection (SSI) criteria by the Centers for Disease Control and Prevention (CDC). We evaluated the infections according to antibiotic use (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…There is uniform agreement that postoperative pain is increased by their use [2,7,9]. According to some studies, Splints were shown to offer no additional help in stabilizing the septum postoperatively and finally, there is the very slight but definite risk of developing the toxic shock syndrome [7,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…There is uniform agreement that postoperative pain is increased by their use [2,7,9]. According to some studies, Splints were shown to offer no additional help in stabilizing the septum postoperatively and finally, there is the very slight but definite risk of developing the toxic shock syndrome [7,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding and infection in septoplasty with or without turbinoplasty were reported to be around 3% in a large study from Poland ( 6 ). In a recent Finnish study, the number of postoperative infections were reduced from 6.1% when no antibiotics were administered to 2.6% with one dose of prophylactic cephuroxime ( 22 ). Preoperative antibiotics in septoplasty is, however, not a standard practice in the Nordic countries.…”
Section: Other Factors That Could Affect the Surgical Outcomementioning
confidence: 99%
“…3 Nonetheless, the introduction of nasal foreign bodies has raised concerns regarding the potential risk of developing local nasal infections and even toxic shock syndrome. 4,5 To minimise the risk of postoperative infections, the practice of prescribing postoperative antibiotic therapy following septoplasty with ISS placement has become increasingly common. 6 However, the available data on the efficacy of prophylactic antibiotic therapy in the presence of ISS are limited, leaving uncertainty about its true benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of ISS, when compared to nasal packing, has been well‐established in improving nasal airflow and enhancing patient comfort, thereby driving its widespread acceptance and implementation in clinical practice 3 . Nonetheless, the introduction of nasal foreign bodies has raised concerns regarding the potential risk of developing local nasal infections and even toxic shock syndrome 4,5 . To minimise the risk of postoperative infections, the practice of prescribing postoperative antibiotic therapy following septoplasty with ISS placement has become increasingly common 6 .…”
Section: Introductionmentioning
confidence: 99%